Essential Mathematics for Economists - Black, John; Bradley, J. F. (London: New York: J. Wiley, 1973)
This book is intended to equip students with the elementary mathematical skills they will need if they are to understand modern quantitative studies based on these theories. In the early chapters especially some very elementary points are spelled out in some detail. This is intended to help readers to whom they are new, and those for whom some reminder of rusty mathematical tools is useful.
Includes index: p. 265-268.
ne 29/03/2018
Loan
Keywords: Economics, Mathematical